2020
DOI: 10.2147/dmso.s275230
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Associated Factors of Diabetes Mellitus Among Adult Population in Hawassa Zuria Woreda, Sidama Region, Ethiopia</p>

Abstract: Background: Diabetes mellitus (DM) is one of the main health problems in unindustrialized countries. According to the International Diabetes Federation report, adults living with diabetes were growing from time to time globally. Worldwide, diabetes mellitus accounts for 8.8% (424.9 million) morbidity and 4 million deaths. Ethiopia is one of the countries frequently affected by the disease with about 2.567 million (5.2%) of its population affected with diabetes mellitus. Objective: This study was aimed at deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
4
13
0
Order By: Relevance
“…The pooled meta-regression analysis revealed a statistically significant difference in the exposure of type-2 DM among normal body mass index and obese with the odds ratio of 1.54 (95%: CI: 1.3, 1.83). Among the studies included in this meta-analysis, older age individuals were more exposed to type-2 diabetes than the younger age group, which is supported by the study 1 , 2 , 5 , 9 , 17 , 18 , 20 , 22 – 24 , 26 , 28 , 32 , 33 , 38 , 51 , 56 . In contrast, our study 11 , 23 , 35 , 45 had got the result that contradict the other studies and concluded age had no any effect over the development of DM.…”
Section: Resultssupporting
confidence: 61%
“…The pooled meta-regression analysis revealed a statistically significant difference in the exposure of type-2 DM among normal body mass index and obese with the odds ratio of 1.54 (95%: CI: 1.3, 1.83). Among the studies included in this meta-analysis, older age individuals were more exposed to type-2 diabetes than the younger age group, which is supported by the study 1 , 2 , 5 , 9 , 17 , 18 , 20 , 22 – 24 , 26 , 28 , 32 , 33 , 38 , 51 , 56 . In contrast, our study 11 , 23 , 35 , 45 had got the result that contradict the other studies and concluded age had no any effect over the development of DM.…”
Section: Resultssupporting
confidence: 61%
“…Fasting blood glucose level was measured using a glucometer. Fasting blood glucose level was taken was measured after the study participants fasted overnight for at least 12 hours [17][18][19].…”
Section: Measurementsmentioning
confidence: 99%
“…Whereas, undiagnostic diabetes was defined as participants whose FBS level was �126 mg/dl on two separate measurements and were unaware of it before the survey [17,19].…”
Section: Plos Onementioning
confidence: 99%
“…
To the Editor: Diabetes mellitus (DM) is a chronic disease that endangers human health and can lead to different complications. [1] Coronary artery disease is one of the most serious complications in DM patients. Recently, increasing evidence has shown that the pathophysiology of diabetic coronary diseases is related to ion channels dysfunction in coronary artery smooth muscle cells (SMCs).
…”
mentioning
confidence: 99%
“…To the Editor: Diabetes mellitus (DM) is a chronic disease that endangers human health and can lead to different complications [1] . Coronary artery disease is one of the most serious complications in DM patients.…”
mentioning
confidence: 99%